Adenocarcinoma of the esophagogastric junction: characteristics of female patients and young adult patients based on a 12-year retrospective and prospective multicenter clinicoepidemiological cohort study in Japan - Kazuhiro Matsueda; Noriaki Manabe; Tetsuo Watanabe; Yoshitaka Sato; Motowo Mizuno; Ken Haruma (BMC Gastroenterology, 2024)
Abstract Background Adenocarcinoma of the esophagogastric junction (AEGJ) is most common in men and the elderly, but the disease is becoming more common in female and young adult persons. We have investigated the clinicoepidemiological characteristics of female and young adult patients with AEGJ and the 12-year trends in the Kurashiki area for young adult patients with AEGJ. Methods Patients diagnosed with AEGJ in 12 hospitals between January 2008 and December 2019 were included in this study. Patients were divided into three groups by age (young adult [≤50 years], middle-aged [51 to 70 years], and elderly [>70 years]). Factors associated with AEGJ such as obesity, smoking, hiatal hernia and male, which were reported in our previous study, were identified. Results One hundred and eighty-eight AEGJ patients, including 36 females and 20 young adults, were characterized. There was no significant change in the annual incidence of AEGJ among female (p=0.078) and young adult patients (p=0.89). Female patients without any associated factors, accounting for 53% (19/36) of the female patients and young adult patients, had significantly more histologically undifferentiated cancers than patients with at least one associated factor (58% [11/19] vs. 30% [50/169], p=0.025) and middle-aged and elderly patients (60% [12/20] vs. 30% [25/83] vs. 28% [24/85], p =0.026). Smoking was significantly less common in women than in men (8% [3/36] vs. 57% [87/152], p < 0.01). There were no significant differences between ages in the proportions of these associated factors. Conclusions Histologically undifferentiated AEGJ cancers were more frequent in female patients without any associated factors and in young adult patients. Factors associated with AEGJ may differ between women and men, but they are similar in young adults and older adults. No increase in young adult patients with AEGJ was observed in the 12-year study.